Normative indicators for an isiXhosa-speaking population with disadvantaged education for tests of hand motor function and verbal fluency - Da Silva Pita, Anita (Rhodes University, Faculty of Humanities, Department of Psychology, 2012)
The aim of the study was to obtain preliminary normative data for two tests of hand motor function (Successive Finger Tapping and Purdue Pegboard tests) and two tests of verbal fluency ("S"-Words-In-One-Minute and Words-In-One-Minute), administered in English, on a non-clinical sample of black, isiXhosa-speaking unskilled workers with a background of relatively disadvantaged former DET education (N = 33). The sample was equally distributed for gender; educational level was restricted to 11 - 12 years; age range was 18 - 40 years divided further into two age categories (18 - 29 and 30 - 40 years). Results of t-test comparative analyses revealed significant age effects on both trials of the Successive Finger Tapping test in the direction of the younger age group outperforming the older age group, and a marginal but consistent tendency towards poorer performance at an earlier age stage than proposed by the available literature, for the Purdue Pegboard, "S"Words- In-One-Minute and Words-In-One-Minute. Gender effects were only in evidence on the Purdue Pegboard in the direction of females outperforming males. A descriptive comparison of the norms acquired for the present study with available normative data for English first language speaking populations with higher levels and/ or relatively advantaged quality of education revealed consistently poorer performance for the present study. The findings highlight the effect of relatively low levels and/ or poor quality of education on both verbal and non-verbal neuropsychological test performance and confirm the need for demographically specific normative data.
Keywords: Neuropsychological tests; Hand -- Movements; People with social disabilities -- Language; People with social disabilities -- Education